Birthright. Volume ten, Epilogue - Williamson, Joshua (Image Comics, 2021)
"When he was a child, Mikey Rhodes disappeared. Lost in the land of Terrenos, he grew into a warrior of legend and waged war against the God King Lore--a war that even ravaged Earth. Now, that war is over, and Mikey is victorious. But no victory is without sacrifice..."--Back cover.